EDITORIAL - Ivan Čuk (University of Ljubljana Press (Založba Univerze v Ljubljani), 2019)
Dear friends, Let me start with the latest news: at the World Championships in Stuttgart (GER), gymnasts from Turkey, Hong Kong, Ireland and the Philippines won medals for their countries for the first time ever. Simone Billes (USA) is now officially the most decorated gymnast at world championships. We saw some excellent gymnastics one year prior to the Olympic Games in Tokyo. Parkour was included in the games. October was really full of events. Additionally, there were two symposiums about gymnastics, one held in Freiburg (GER) and one in Osaka (JPN). In Slovenia, our Olympic champion Miroslav Cerar is celebrating his 80th birthday this year and as a gift, his club (established in 1863) set up an exhibition about his achievements in the Ljubljana City Hall.     In this issue, we have seven articles by authors from the USA, Greece, the United Kingdom, Slovenia, Finland and Brazil. The first article is about trampolining. It is authored by an international group of researchers lead by William A. Sands (USA). The second article is from Slovene authors; they discus symmetries at take-offs and landings. The third article is from Greece and is about anxiety in young male gymnasts. The fourth article comes from Finland and looks at the relationship between test motor abilities, technical knowledge and competition results. The fifth article is from Brazil and examines the importance of rhythmics in university programmes. From Greece comes another article, about diet in rhythmics and aerobics. The last article is from Brazil and is about choreography in gymnastics for all.      Anton Gajdoš drafted another article related to the history of gymnastics, refreshing our awareness of Miroslav Cerar, an excellent Slovene (formerly Yugoslav) gymnast.   Just to remind you, if you quote the Journal, its abbreviation on the Web of Knowledge is SCI GYMN J.   I wish you pleasant reading and a lot of inspiration for new research projects and articles,   Ivan Čuk     Editor-in-Chief